Pendampingan Perhitungan Unit Cost Di Lingkungan Rumah Sakit - helmy adam (P3M Politeknik Negeri Malang, 2023)
This assistance aims to assist Menur Mental Hospital in calculating the unit cost in determining the rate of charge to patients in accordance with the actual service costs. The method used in this service is a case study with data collection methods in the form of observation through focus group discussions, interviews and documentation. The analysis used is quantitative based on data interpretation by delivering information in the form of texts and narratives. The analysis used or grand theory. Results of Community Service. From the results of the analysis, it is found that several things that need to be considered regarding unit cost calculations in RJS Menur are the establishment of standardization to determine direct and indirect costs that will be calculated in unit cost calculations. This is because there is still no standardization of quality, cost and so on which appears as one of the problems in the unit cost analysis process.